Improving identification of coppiced and seeded trees in past woodland management by comparing growth and wood anatomy of living sessile oaks (Quercus petraea). (10th January 2018) - Girardclos, Olivier; Dufraisse, Alexa; Dupouey, Jean-Luc; Coubray, Sylvie; Ruelle, Julien; Rathgeber, Cyrille B.K.
Abstract: Written sources and archaeological evidence suggest that coppicing was a common practice in past woodland management. Depending mainly on the length of rotations, coppices provided wood products of various sizes, and coppice-wood has been identified in fuel-wood remains as well as in timber studies. Assigning the origin of the wood analyzed to coppice is based on observation of "typical growth patterns": an even-age structure and a rapid decrease in ring-width with age are used nowadays. However, the wide variety of coppice practices and the variability observed in living-tree analogs make it difficult to draw definitive conclusions. To contribute to improving coppice-wood identification, the present study analyzed differences in growth and tree-ring anatomy between living sessile oaks from a mixed stand of coppiced and seeded trees. Stems were compared based on ring-width, early- and late-wood widths, number and size of the earlywood vessels, and tissue proportions measured at different heights. The growth of coppiced trees was found to be faster than that of seeded trees, in height at cambial ages between 3 and 5 years and in diameter at 5–8 years. A quantitative anatomy study showed that tree rings from coppice shoots had smaller and more numerous vessels per unit surface area and a weaker hydraulic conductivity. Earlywood width, which can be acquired on archaeological wood much more easily than vessel surface, was significantly greater in the sample of seeded trees. Linear discriminant analysis performed on the data used to model earlywood width (leave-one-out procedure) correctly classified 77% of coppice and 54% of seeded trees when the radius exceeded 1.66 cm and offers promising perspectives for dendro-anthracology and dendrochronology. Growth and anatomical differences between coppiced and seeded trees mixed in the same stand were observed while other sources of variability (site condition, competition, species) were constrained.